Tekhnik Matriconditioning Arang Sekam Padi Terhadap Pertumbuhan Dan Hasil Kedelai (Glycine max L.Merill) Asal Benih Kedaluwarsa - Nurhidayah, Selvi; Mapegau, Mapegau; Riduan, Ahmad (Universitas Batanghari, 2025)
Soybeans are a plant that has great opportunities and promising prospects to be cultivated, but there are often problems in this cultivation such as the problem of seed setback. The gradual process of degradation of seed quality and vitality, known as seed deterioration, cannot return to its original state or be restored. Soybean seeds that have expired so far are no longer used, because their short shelf life makes them only usable for consumption. Using invigoration techniques is one method to control seed setback. Matriconditioning is a treatment that utilizes moist solid media, such as charcoal, husks, and sawdust. This research aims to investigate the effect of husk charcoal on the viability and vigor of soybean seeds, as well as its effects on soybean growth and yield (Glycine max (L). Merril). This research lasted about 4 months, starting in November 2022, , and was carried out at the Seed Technology Laboratory and Teaching and Research Farm, Faculty of Agriculture, University of Jambi and was carried out in two stages. This research was carried out simultaneously, namely Phase I of the research was carried out in the laboratory, while Phase II was carried out in the field. The results of the study showed that invigoration treatment with matriconditioning had a significant effect on germination power, maximum growth potential, normal germination dry weight, and growth speed. The treatment of planting media has a real effect on the weight of planting seeds and the number of pods per plant. Matriconditioning treatment had no noticeable effect on plant height, dry weight of the plant, root nodules, seed weight per plant, and number of pods per plant. Matriconditioning treatment has a real effect on the leaf area index.